A scaffold laden with mesenchymal stem cell-derived exosomes for promoting endometrium regeneration and fertility restoration through macrophage immunomodulation. (1st September 2020) - Xin, Liaobing; Lin, Xiaona; Zhou, Feng; Li, Chao; Wang, Xiufen; Yu, Huaying; Pan, Yibin; Fei, Haiyi; Ma, Lie; Zhang, Songying
Abstract: Endometrial traumas may cause intrauterine adhesions (IUAs), leading to infertility. Conventional methods in clinic have not solved the problem of endometrial regeneration in severe cases. Umbilical cord-derived mesenchymal stem cell (UC-MSC)-based therapies have shown some promising achievements in the treatment of IUAs. However, the limitations of potential tumorigenicity, low infusion and low retention are still controversial and restricted the clinical application of MSCs. In contrast, UC-MSC-derived exosomes exhibit a similar function to their source cells and are expected to overcome these limitations. Therefore, a novel and viable cell-free therapeutic strategy by UC-MSC-derived exosomes was proposed in this study. Here, we designed a construct of exosomes and collagen scaffold (CS/Exos) for endometrial regeneration in a rat endometrium-damage model, and investigated the regeneration mechanism through macrophage immunomodulation. The CS/Exos transplantation potently induced (i) endometrium regeneration, (ii) collagen remodeling, (iii) increased the expression of the estrogen receptor α/progesterone receptor, and (iv) restored fertility. Mechanistically, CS/Exos facilitated CD163 + M2 macrophage polarization, reduced inflammation, and increased anti-inflammatory responses in vivo and in vitro . By RNA-seq, miRNAs enriched in exosomes were the main mediator for exosomes-induced macrophage polarization. Overall, we demonstrated that CS/Exos treatment facilitated endometrium regeneration and fertility restoration by immunomodulatory functions of miRNAs. Our research highlights the therapeutic prospects of CS/Exos for the management of IUAs. Statement of significance: Severe endometrial traumas always result in intrauterine adhesions (IUAs) and infertility. The limited outcomes by conventional methods in the clinic make it very important to develop new strategies for endometrium regeneration and fertility restoration. In this study, an exosome-laden scaffold (CS/Exos) was designed and the transplantation of CS/Exos potently induced (i) endometrium regeneration, (ii) collagen remodeling, (iii) increased the expression of the estrogen receptor α/progesterone receptor, and (iv) restored fertility. In mechanism, the construct of CS/Exos facilitated M2 macrophage polarization, reduced inflammation, and increased anti-inflammatory responses. Furthermore, miRNAs enriched in exosomes were the main mediator for exosome-induced macrophage polarization. This study highlights the therapeutic prospects of CS/Exos and the translational application for the management of severe IUAs. Graphical abstract: Image, graphical abstract